The Political Properties of Crystalline H2O: Planning for Snow Emergencies in New York - Savas, E. S. (Management Science, 1973)
A major snowstorm produced a serious snow emergency and a political crisis in New York City. Mayor Lindsay asked for an analysis of the problem to prevent its recurrence. His management science unit studied four basic questions: (1) How much snow falls on New York City? (2) How much work has to be done to clean it up? (3) What is the capacity for performing this work? (4) What improvements are needed to correct any imbalance between work load and work capacity? The surprising findings eliminated most of the remedies that had been offered earlier. A low-cost snow emergency plan was prepared, calling for some additional equipment, better deployment, and a strategy for more rapid mobilization. The recommendations were implemented promptly, and with due regard for political impact, in the midst of a mayoralty election campaign.